I Peningkatan Kualitas Hidup Pasien Diabetes Melitus Dengan Senam Diabetes Di Wilayah Kerja Puskesmas Depok II Sleman - Erika Nurwidiyanti; Ni Ketut Kardiyudiyani; Gede Suka Mandiarta (J.Abdimas: Community Health, 2022)
The prevalence of Diabetes Mellitus (DM) patients continues to increase every year, it requires attention because it can decrease the quality of life for sufferers. Quality of life in people with diabetes can be improved by doing sports, one of which is diabetes exercise. The results of a preliminary study on 5 DM patients at Puskesmas Depok II found that 3 patients had a poor quality of life and 2 patients had a fairly good quality of life. The method of this implementation service is teach and apply diabetes exercises to DM sufferers by involving local cadres and conducting pre and post-tests to measure the quality of life of sufferers. The results of the activity showed that there was an increase in the quality of life of the participants, namely before they did diabetes exercise, 4 participants of 37 DM patients had a good quality of life (10.8%), 23 participants had a fairly good quality of life (62.2%), and 10 participants had a poor quality of life (27%). After they did diabetes exercise, the percentage of participants who had a good quality of life increased to 6 participants (16.2%) and the quality of life was quite good for 29 participants (78.4%), while participants with poor quality of life decreased to 2 participants (5,4%). It can be concluded that diabetes exercise needs to be implemented because it can improve the quality of life in DM patients. Keywords: Diabetes Exercise, Quality of Life, Diabetes Mellitus